2013
DOI: 10.1016/j.actbio.2012.09.031
|View full text |Cite
|
Sign up to set email alerts
|

On the biomechanical role of glycosaminoglycans in the aortic heart valve leaflet

Abstract: While the role of collagen and elastin fibrous components in heart valve valvular biomechanics has been extensively investigated [see Sacks et al. 2009 J. Biomech. 42, 1804-24], the biomechanical role of the glycosaminoglycan (GAG) gelatinous-like material phase remains unclear. In the present study, we investigated the biomechanical role of GAGs in porcine aortic valve (AV) leaflets under tension utilizing enzymatic removal. Tissue specimens were removed from the belly region of porcine AVs and subsequently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…While there were minimal differences between genotypes at each age (supporting previous studies negating the role of PGs and GAGs in tendon mechanics), there were changes with the effect of aging on those properties and changes in the realignment of collagen fibers. Recent studies suggest that GAGs and PGs may play a bigger role in fiber-fiber and fiber-matrix interactions at low strain levels, which is supported in this study, where changes in fiber re-alignment were found at small strain changes, such as preconditioning and in the toe region [28]. Overall, this data suggests that mechanical property measurements alone do not fully account for the functional changes that occur with structural alterations, especially when concerning alterations at much lower hierarchical levels.…”
Section: Days 300 Days 570 Dayssupporting
confidence: 87%
“…While there were minimal differences between genotypes at each age (supporting previous studies negating the role of PGs and GAGs in tendon mechanics), there were changes with the effect of aging on those properties and changes in the realignment of collagen fibers. Recent studies suggest that GAGs and PGs may play a bigger role in fiber-fiber and fiber-matrix interactions at low strain levels, which is supported in this study, where changes in fiber re-alignment were found at small strain changes, such as preconditioning and in the toe region [28]. Overall, this data suggests that mechanical property measurements alone do not fully account for the functional changes that occur with structural alterations, especially when concerning alterations at much lower hierarchical levels.…”
Section: Days 300 Days 570 Dayssupporting
confidence: 87%
“…109 These proteins do not provide the same stiffness of collagen; however, they are highly polar and attract water, which serves as a lubricnt cushion to absorb compressive stresses in the tissue. 110 In addition, proteoglycans and GAGs can help sequester, or function as coligands, for growth factors. 95 In CAVD, proteoglycans and GAGs might contribute to atherosclerotic lesion development by retaining lipids accumulation and attraction inflammatory cells in the valve ECM.…”
Section: The Extracellular Matrixmentioning
confidence: 99%
“…It is observed that chemically crosslinking pericardium damages and distorts the natural structure, destroys interstitial cells, and diminishes potential for viable cell inhabitation. 13 The specialized matrix consisting of collagen, elastin, and glycosaminoglycans (GAGS) that compose the pericardium is responsible for allowing the tissue to accommodate the constant changes in shape and stress transfer, 13,14 and is therefore essential to maintain. Damaging this natural structure and removing native cells results in a tissue that can no longer maintain or repair itself.…”
mentioning
confidence: 99%